Correlation between parathyroid function and serum levels of 1,25(OH)2D3, serum phosphorus, and parathyroid hormone after surgery for papillary thyroid carcinoma: Surgery for papillary thyroid carcinoma - Wang, Bo; Gu, Lei; Liu, Jun (Cellular and Molecular Biology, 2023)
The objective of this work was to investigate the factors influencing parathyroid function (PTF) after surgery for papillary thyroid carcinoma (PTC) and the relationship of serum 1,25(OH)2D3 and serum phosphorus to parathyroid hormone (PTH) levels. 113 patients with papillary thyroid carcinoma (PTC) were enrolled, including 75 patients with lowered PTF (70 patients with temporary (temporary reduction group) and 5 patients with permanent (permanent reduction group)) and 38 patients with normal PTF (normal group). The results of detection indexes showed that the serum PTH levels were decreased to different degrees compared with those before surgery. Serum 1,25(OH)2D3 levels decreased less in the normal group before and after surgery but decreased more in the temporary and permanent reduction groups. The change range of blood phosphorus before and after the surgery was small in the normal group, and the increase ranges in the temporary and permanent reduction groups were larger. The lowered PTF was negatively correlated with age and blood phosphorus (P<0.01) but positively correlated with serum PTH (P<0.05) and serum 1,25(OH)2D3 (P<0.01). In conclusion, lowered PTF after surgery for PTC was negatively correlated with blood phosphorus, which can indicate a decrease in PTH levels in patients. Meanwhile, the lowered PTF was positively correlated with serum PTH and serum 1,25(OH)2D3 levels.